PON-1 Activity and Plasma 8-Isoprostane Concentration in Patients with Angiographically Proven Coronary Artery Disease. (30th November 2015) - Kuchta, Agnieszka; Strzelecki, Adrian; Ćwiklińska, Agnieszka; Totoń, Magdalena; Gruchała, Marcin; Zdrojewski, Zbigniew; Kortas-Stempak, Barbara; Gliwińska, Anna; Dąbkowski, Kamil; Jankowski, Maciej
Abstract : The aim of the study was to estimate association of the extent of angiographically proven coronary artery disease (CAD) with plasma 8-isoprostane F2 (8-iso-PGF2 α ) levels as a reliable marker of lipid peroxidation and serum activity of paraoxonase-1, which demonstrates the ability to protect against lipid oxidation. The study included 105 patients with angiographically documented CAD (CAD+) and 45 patients with negative results of coronary angiography (CAD−). Compared to the control group CAD+ patients were characterized by increased 8-iso-PGF2 α levels (P = 0.007 ) and reduced activity of PON-1 towards paraoxon (PONase, P = 0.002 ) and phenyl acetate (AREase, P = 0.037 ). Univariate correlation analysis indicated that 8-iso-PGF2 α concentrations were positively associated with the severity of CAD as evaluated by the Gensini score (R = 0.41, P < 0.001 ) while PONase activity (R = − 0.26, P < 0.05 ) and AREase activity (R = − 0.23, P < 0.05 ) were inversely correlated with CAD severity. PONase activity and 8-iso-PGF2 α concentration remained independent determinant of atherosclerosis severity in multiple linear regression after adjusting for age, gender, smoking habits, hypertension, type 2 diabetes, statin therapy, and HDL-C and TAG concentration (β coefficients −0.267;P < 0.05 and 0.368;P < 0.001, resp.). The results suggest that PON-1 activity and 8-iso-PGF2 α concentration are associated with the presence and extent of coronary stenosis and may be considered additional markers of coronary artery disease.